What is an appropriate caesarean delivery rate for China: a multicentre survey. (26th October 2021) - Zhang, Y; Betran, AP; Li, X; Liu, D; Yuan, N; Shang, L; Lin, W; Tu, S; Wang, L; Wu, X; Zhu, T; Zhang, Y; et al.
Abstract : Objective: To assess the current status of caesarean delivery (CD) in China, propose reference CD rates for China overall, and by regions, investigate the main indications for CDs and identify possible areas for safe reduction. Design: A multicentre cross‐sectional study. Setting: A total of 94 hospitals across 23 provinces in China. Population: A total of 73 977 randomly selected deliveries. Methods: We used a modified Robson classification to characterise CDs in subgroups and by regions, and the World Health Organization (WHO) C‐Model to calculate reference CD rates. Main outcome measures: CD rates in China. Results: In 2015–2016, the overall CD rate in China was 38.9% (95% CI 38.6–39.3%). Considering the obstetric characteristics of the population, the multivariable model‐based reference CD rate was estimated at 28.5% (95% CI 28.3–28.8%). Accordingly, an absolute reduction of 10.4% (or 26.7% relative reduction) may be considered. The CD rate varied substantially by region. Previous CD was the most common indication in all regions, accounting for 38.2% of all CDs, followed by maternal request (9.8%), labour dystocia (8.3%), fetal distress (7.7%) and malpresentation (7.6%). Overall, 12.7% of women had prelabour CDs, contributing to 32.8% of the total CDs. Conclusions: Nearly 39% of births were delivered by caesarean in China but a reduction of this rate by a quarter may be considered attainable. Repeat CD contributed more than one‐third of the total CDs. Given the large variation in maternal characteristics, region‐specific or even hospital‐specific reference CD rates are needed for precision management of CD. Tweetable abstract: The caesarean rate in 2015–2016 in China was 38.9%, whereas the reference rate was 28.5%. Tweetable abstract: The caesarean rate in 2015–2016 in China was 38.9%, whereas the reference rate was 28.5%. Linked article This article is commented on by M Varner, p. 148 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.16953 .